A comparative analysis of the kayak forward stroke - Skopek, M.; Bacakova, R.; Bily, M.; Tunkova, K. (Physical Activity Review, 2019)
Introduction: This work follows previous research in the field which investigated the comparison of two types of paddling. These studies, however, focused on the similarity of kayaking and trainers, more precisely ergometers, that are used by racers during their training in the winter. However, the results of these studies indicate a significant difference in muscle involvement. Aim of Study: The aim of this study is to describe and to compare the muscle activation of the kayak forward stroke performed in a pool with an opposite/counter current and on flat/calm water. Material and Methods:The research was conducted via a selected sample of eight kayakers (subjects) who had attained a high level of performance in whitewater slalom. We observed the activity of twelve selected muscles used during the kayak forward stroke performed in a counterflow pool and on flat water by means of surface electromyography and kinematic analysis. Study results point to effects in relation to intra-individual and subsequently inter-individual muscle timing and the size of the muscle activation due to maximal voluntary contraction. We used comparative analysis and the data were measured by surface electromyography and 2D video-analysis.Results: The results proved equal timing of muscles in a counterflow pool and on flat water. The muscle activity in the counterflow pool was bigger than on flat water.Conclusion: From our results we can recommend a pool which makes use of a counter current as a replacement training tool. Compared with other training devices which might be used (such as, crank ergometers, paddling trainers, and paddling pools), this kind of training device gives the kayaker one great advantage. It is the fact that the kayaker has the same placement of the fixed point and the preservation of the feeling of grasping water.